PENGARUH PEMBERIAN MADU HUTAN TERHADAP PROLIFERASI LIMFOSIT PADA HEWAN UJI TIKUS JANTAN GALUR WISTAR - Kartika Sari Senas; Yunita Linawati (Universitas Sanata Dharma, 2012)
Abstract: Forest honey is produced by wild bees by taking nectars from several kinds of plant. One of active chemicals contained within honey is flavonoid. It is believed as an immunomodulator due to it has role in fighting against free radicals and increasing body immune system against disease infection. This research aimed to understand the influences of forest honey administration to the lymphocyte proliferation on male mice Wistar family. This research is a pure, experimental with one way, random research design. Total of 20 rats was divided into 4 groups. Each group was given honey forest with dose of 0,27; 0.54; 1.08 mL/200 g BW, and negative control group was given aquadest 2.5 mL/200 g BW. The lymphocyte proliferation is measured from the amount of lymphocyte based on Optical Density (OD) values, the read on ELISA reader at the wavelength of 550 nm. The result shown that the administration of forest honey has effect on significance increase the lymphocyte proliferation (p<0.05) than negative control on male mice Wistar family. Key words : Foresthoney, lymphocyte proliferation, immunomodulator